The soybean plasma membrane‐localized cation/H+ exchanger GmCHX20a plays a negative role under salt stress. Issue 4 (6th November 2020) - Jia, Qi; Li, Man‐Wah; Zheng, Chengwen; Xu, Yiyue; Sun, Song; Li, Zhong; Wong, Fuk‐Ling; Song, Junliang; Lin, Wei‐Wei; Li, Qinghua; Zhu, Yebao; Liang, Kangjing; et al.
Abstract: Cation/H + ‐exchanger (CHX) perform diverse functions in plants, including being a part of the protective mechanisms to cope with salt stress. GmCHX1 has been previously identified as the causal gene in a major salt‐tolerance quantitative trait locus (QTL) in soybean, but little is known about another close paralog, GmCHX20a, found in the same QTL. In this study, GmCHX20a was characterized along with GmCHX1 . The expression patterns of the two genes and the direction of Na + flux directed by overexpression of these two transporters are different, suggesting that they are functionally distinct. The ectopic expression of GmCHX20a led to an increase in salt sensitivity and osmotic tolerance, which was consistent with its role in increasing Na + uptake into the root. Although this seems counter‐intuitive, it may in fact be part of the mechanism by which soybean could counter act the effects of osmotic stress, which is commonly manifested in the initial stage of salinity stress. On the other hand, GmCHX1 from salt‐tolerant soybean was shown to protect plants via Na + exclusion under salt stress. Taken together these results suggest that GmCHX20a and GmCHX1 might work complementally through a concerted effort to address both osmotic stress and ionic stress as a result of elevated salinity.